PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP POLA PERILAKU KOMUNIKASI SISWA SMA AR-RAHMAN MEDAN - Sangkar Rezeki Hasibuan; Solihah Titin Sumanti; Fakhrur Rozi (Lafadz Jaya Publisher, 2023)
The purpose of this study is to determine the effect of the use of social media and to determine how much influence occurs between the use of social media. social media and to find out how much influence occurs between the use of social media on student communication behavior patterns at ArRahman Medan High School. This research uses quantitative research which aims to determine the effect of Social Media Use on Student Communication Behavior Communication Behavior of Students at Ar-Rahman High School Medan. This research will involve 2 (two) variables, namely variable Y: communication behavior and variable X: social media. social media. From the results of the research, the researcher can conclude two things, namely the variable the use of social media has a significant effect on Communication behavior of Ar-Rahman Medan Private High School students and the amount of influence given by the use of social media is 51.5 percent. Given by the use of social media is 51.2% on Communication Behavior, which means there is still 48.2%. Communication Behavior, which means that there are still 48.2% other factors that can influence the Communication Behavior of students.